A SEMEIOLOGICAL ANALYSIS SAMPLE: THE WATCHTOWER OF TURKEY - Mustafa AKBAYIR; Aslıhan DUMLU (International Journal of Eurasia Social Sciences, 2017)
In the study a mini documentary series, that have become a viral in internet from the moment it was published in 2014 is analyzed. This video named The Watchtower of Turkey was broadcasted by Leonardo Dalessandri, an Italian director, and it is about Turkey is analyzed semeiologically. The study firstly focuses on its theoritic part.By doing some literature search,the general information is combined with the semeiology which is the main point of this study. And then a detailed information about the director and his studies which are the main points of this work is presented.With the end of theoritic part Roland Barthes' video at issue is analyzed according to the semeiological analysis method. After the discussion of the information gathered, subjective opinions are mentioned and some advice is given. The original purpose of this study is to research thoroughly the new media’s speed and its effect power in means of cultural studies ecole. Therefore, study focuses on The Watchtower of Turkey video which broadcasts cultural patterns with an oreintalist point of view.